2015
DOI: 10.1080/19381980.2015.1063751
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of soybean isoflavone as antiandrogen on acne vulgaris

Abstract: Background: Acne vulgaris (AV) is the commonest skin disorder, whereas soybean isoflavone had been proved as antiandrogen that is it can inhibit the enzyme 3ß-hydroxysteroid dehydrogenase,17ß-hydroxysteroid dehydrogenase and 5α-reductase. The purpose of this study is to prove the advantage of soybean isoflavone as antiandrogen on AV. Methods: this study is a clinical study using randomized pretest-posttest control group design. This study is a study with 40 samples randomized into 2 groups, i.e. placebo group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Tretinoin is a topical retinoid that was proven effective as monotherapy, and has been the first drug of choice for mild and moderate AV [2,3]. Another study concerning the effect of soy isoflavone on in vitro human prostate cancer cell cultures has demonstrated that isoflavone will reduce the expression of TNF-and an animal model has demonstrated that isoflavone can inhibit the inflammatory response, by inhibiting the NFB, MAP kinase and several cellular signaling pathways, and thus reducing the expression of several pro-inflammatory cytokines, such as IL-1, IL-8 and TNF- [1] (Figure 2). Studies had proven that soy isoflavone could affect the androgen system.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Tretinoin is a topical retinoid that was proven effective as monotherapy, and has been the first drug of choice for mild and moderate AV [2,3]. Another study concerning the effect of soy isoflavone on in vitro human prostate cancer cell cultures has demonstrated that isoflavone will reduce the expression of TNF-and an animal model has demonstrated that isoflavone can inhibit the inflammatory response, by inhibiting the NFB, MAP kinase and several cellular signaling pathways, and thus reducing the expression of several pro-inflammatory cytokines, such as IL-1, IL-8 and TNF- [1] (Figure 2). Studies had proven that soy isoflavone could affect the androgen system.…”
Section: Discussionmentioning
confidence: 99%
“…Soy isoflavone used in this study was an extract of soy isoflavone produced and standardized by the pharmaceutical industry Nu-Health, California, United States of America. The treatment group was given 2 capsules; each capsule held 400 mg of soy isoflavone extract containing 80 mg of pure isoflavone [1]. Inclusion criteria were female AV patients for the last 3 months, not under any medication, and willing to participate in the study by signing the informed consent form.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations